Effects of dietary inclusion of sun-dried or roasted stranded fish on egg-type pullet growth and egg laying of hens - Babiker, Mutaz S.; S. Mansour, Sara M.; Morkaz, Mohammed G. (Gezira Journal of Agricultural Science; Vol 17 No 2 (2019), 2019)
The objective of the study was to measure the effect of the substitution of imported super concentrate by different levels of locally produced fishmeal on pullet’s growth and egg laying performance. Different types of stranded fish from the White Nile, Sudan, were collected during March and April 2017, ground and then sun-dried (A) or roasted (B). The experimental diets were iso-energetic and iso-nitrogenous to meet or exceed the requirements of pullets growing phases (starter, grower and developer) and laying. The dried or roasted fish (fishmeal) were used to replace the imported protein concentrates at three levels. The sun-dried fish (A) consisted of A1 with 1.5% locally sun-dried fishmeal (L.S.F) and 3.5% imported concentrate (I.C.), A2 with 3.5 % (L.S.F) and 1.5% (I.C) and A3 with 5 % (L.S.F) and 0% (I.C). Similarly, the roasted fish (B) consisted of B1 with 1.5 % locally roasted fishmeal (L.R.F) and 3.5% (I.C.), B2 with 3.5 % (L.R.F) and 1.5 % (I.C) and B3 with 5 % (L.R.F) and 0 % (I.C). The control diet contained 0% local fishmeal (C). A total of 210 one day-old (Hy-Line W-98) pullets were allotted to these seven treatments which were replicated three times with ten birds each. The results showed that at the end of the entire growing period, birds fed the sun-dried fishmeal (A) had the highest body weight, weight gain and feed consumption followed by birds fed on (B) diets. The birds fed on control diets (C) consumed numerically the least feed and had the lightest body weight. The highest body weight and weight gain values were recorded with A1 treatment.  At the end of the starter period, the birds fed with B1, B2 and A3 had the lowest levels of blood cholesterol. The birds fed the control and B1 diets had the highest blood cholesterol. At the end of developer period, cholesterol, triglyceride, uric acid and calcium were not significantly affected by treatments. There were no significant differences between sun-dried and roasted fish in hen-day egg production during early weeks of production, however, hens fed the control diet produced less eggs compared with sun-dried treatments during the early production period. It is recommended to replace the super concentrate with 70% sun-dried fish.